Racial/ethnic differences in the epidemiology of ovarian cancer: a pooled analysis of 12 case-control studies. (2nd December 2017) - Peres, Lauren C; Risch, Harvey; Terry, Kathryn L; Webb, Penelope M; Goodman, Marc T; Wu, Anna H; Alberg, Anthony J; Bandera, Elisa V; Barnholtz-Sloan, Jill; Bondy, Melissa L; Cote, Michele L; Funkhouser, Ellen; et al.
Abstract: Background: Ovarian cancer incidence differs substantially by race/ethnicity, but the reasons for this are not well understood. Data were pooled from the African American Cancer Epidemiology Study (AACES) and 11 case-control studies in the Ovarian Cancer Association Consortium (OCAC) to examine racial/ethnic differences in epidemiological characteristics with suspected involvement in epithelial ovarian cancer (EOC) aetiology. Methods: We used multivariable logistic regression to estimate associations for 17 reproductive, hormonal and lifestyle characteristics and EOC risk by race/ethnicity among 10 924 women with invasive EOC (8918 Non-Hispanic Whites, 433 Hispanics, 911 Blacks, 662 Asian/Pacific Islanders) and 16 150 controls (13 619 Non-Hispanic Whites, 533 Hispanics, 1233 Blacks, 765 Asian/Pacific Islanders). Likelihood ratio tests were used to evaluate heterogeneity in the risk factor associations by race/ethnicity. Results: We observed statistically significant racial/ethnic heterogeneity for hysterectomy and EOC risk ( P  = 0.008), where the largest odds ratio (OR) was observed in Black women [OR = 1.64, 95% confidence interval (CI) = 1.34–2.02] compared with other racial/ethnic groups. Although not statistically significant, the associations for parity, first-degree family history of ovarian or breast cancer, and endometriosis varied by race/ethnicity. Asian/Pacific Islanders had the greatest magnitude of association for parity (≥3 births: OR = 0.38, 95% CI = 0.28–0.54), and Black women had the largest ORs for family history (OR = 1.77, 95% CI = 1.42–2.21) and endometriosis (OR = 2.42, 95% CI = 1.65–3.55). Conclusions: Although racial/ethnic heterogeneity was observed for hysterectomy, our findings support the validity of EOC risk factors across all racial/ethnic groups, and further suggest that any racial/ethnic population with a higher prevalence of a modifiable risk factor should be targeted to disseminate information about prevention.